2001
DOI: 10.1093/jac/47.5.709
|View full text |Cite
|
Sign up to set email alerts
|

Suppressive effect of Lactobacillus gasseri OLL 2716 (LG21) on Helicobacter pylori infection in humans

Abstract: To examine the efficacy of Lactobacillus gasseri OLL2716 (LG21) as a probiotic for Helicobacter pylori in humans, 31 subjects infected with the bacterium ingested yogurt containing LG21 daily for an 8 week period. The [(13)C]urea breath test and assays of serum pepsinogens revealed a significant improvement following LG21 treatment. LG21 was thus determined to be effective in both suppressing H. pylori and reducing gastric mucosal inflammation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
140
4
9

Year Published

2006
2006
2013
2013

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 268 publications
(165 citation statements)
references
References 5 publications
(7 reference statements)
10
140
4
9
Order By: Relevance
“…The effect of 90 g of yogurt with L. gasseri OLL2716 (LG21) administered twice daily for 8 weeks in 29 asymptomatic adults was evaluated by means of the 13 C-UBT and the pepsinogen I/ II ratio as a marker of gastric inflammation. 55 LG21 decreased significantly DOB values in comparison with baseline measurements and reduced the intensity of gastric inflammation as indicated by the lower pepsinogen I/II ratio. Similar results were obtained with LG21 in children.…”
mentioning
confidence: 81%
“…The effect of 90 g of yogurt with L. gasseri OLL2716 (LG21) administered twice daily for 8 weeks in 29 asymptomatic adults was evaluated by means of the 13 C-UBT and the pepsinogen I/ II ratio as a marker of gastric inflammation. 55 LG21 decreased significantly DOB values in comparison with baseline measurements and reduced the intensity of gastric inflammation as indicated by the lower pepsinogen I/II ratio. Similar results were obtained with LG21 in children.…”
mentioning
confidence: 81%
“…These findings lead to the speculation that we are supposed to domesticate H pylori through restoring the homeostasis of the gastric microecosystem. It was reported that administration of exogenous Lactobacilli has therapeutic effects on H pylori-associated diseases by interfering with the pathogenetic progress of H pylori [27][28][29][30] . Inhibition of H pylori-induced proinflammatory factor production by Lactobacilli is a very important aspect.…”
Section: Viable Lbg or Lbg-s Inhibited H Pyloriss1-lps-induced Il-8 Pmentioning
confidence: 99%
“…Los estudios actuales que analizan la colonización del estómago por lactobacilos utilizan alimentos probióticos que contienen cepas de origen intestinal, cuyo mecanismo de protección frente a la colonización por H pylori es desconocido [38][39][40] .…”
Section: Discussionunclassified